A proposal of a new material for greenhouses on the basis of numerical, optical, thermal and mechanical approaches - Sfarra S. Stefano; Perilli S.; Ambrosini D. Dario; Paoletti D. Domenica; Nardi I.; De Rubeis T. Tullio; Santulli C. Carlo (2017, 2017)
Title screen